Prevalence and impact of sarcopenia on urinary incontinence in localized prostate cancer patients undergoing laparoscopic radical prostatectomy - Gu, Tengfei; Li, Jie; Wu, Dan; Chen, Ting; Pan, Yongtao; Yu, Qinzhou; Sha, Jing (Frontiers in Urology, 2025)
ObjectiveThis research seeks to assess the prevalence of sarcopenia in patients diagnosed with localized prostate cancer and to investigate the influence of sarcopenia on the incidence of urinary incontinence following laparoscopic radical prostatectomy.MethodsA cohort of 350 patients, diagnosed with prostate cancer and having undergone laparoscopic radical prostatectomy at our hospital’s urology department between January 2022 and December 2023, was selected for this study. The cohort comprised 215 patients classified as low to intermediate risk and 135 patients classified as high risk. Participants were categorized into two groups: the sarcopenia group (n = 143) and the non-sarcopenia group (n = 207). The study aimed to summarize the prevalence of sarcopenia among patients with localized prostate cancer and to compare the incidence of urinary incontinence immediately post-surgery, as well as at three and six months postoperatively, between the sarcopenia and non-sarcopenia groups.ResultsThe study assessed the prevalence of sarcopenia in a cohort of 350 patients with localized prostate cancer, revealing an overall prevalence rate of 40.86%. Specifically, the prevalence was 34.2% among patients classified as low to intermediate risk and 51.11% among those classified as high risk (P<0.01). The incidence rates of urinary incontinence were documented at various postoperative intervals: immediately after surgery, at 3 months, and at 6 months, with rates of 72%, 47.81%, and 28%, respectively. Notably, patients with sarcopenia exhibited significantly higher urinary incontinence rates compared to those without sarcopenia, at 82.52%, 65.03%, and 37.06% versus 64.73%, 35.75%, and 21.74% (P<0.01). Among low to intermediate-risk patients, the urinary incontinence rates immediately post-surgery, at 3 months, and at 6 months were 59.53%, 32.56%, and 16.28%, respectively, which were significantly lower than the rates observed in high-risk patients, recorded at 91.85%, 71.85%, and 46.67% (P<0.01). In the subgroup of low to intermediate-risk patients with sarcopenia, the postoperative urinary incontinence rates were 68.92% immediately, 54.05% at 3 months, and 18.92% at 6 months, compared to 54.61%, 21.28%, and 14.89% in patients without sarcopenia. However, the differences in incontinence rates immediately post-surgery and at 6 months were not statistically significant (P>0.05)In patients at high risk with sarcopenia, the incidence rates were 97.10%, 76.81%, and 56.52%, which were higher compared to those without sarcopenia, who exhibited rates of 86.36%, 66.67%, and 36.36%. There was no significant difference observed at three months post-surgery (P > 0.05). Regression analysis indicates that sarcopenia is significantly associated with an increased risk of urinary incontinence following radical prostatectomy at three months post-operation (OR = 0.448, 95% CI: 0.290-0.691, P < 0.001) and six months post-operation (OR = 0.175, 95% CI: 0.105-0.291, P < 0.001). After adjusting for confounding factors such as age, tumor risk stratification, diabetes, and pelvic floor function scores, sarcopenia remains an independent predictor of urinary incontinence occurrence at three months post-operation (OR = 0.320, 95% CI: 0.187-0.546, P < 0.001) and six months post-operation (OR = 0.398, 95% CI: 0.224-0.708, P = 0.002).ConclusionsSarcopenia significantly contributes to urinary incontinence following laparoscopic radical prostatectomy and impacts the recovery process, especially in patients with high-risk prostate cancer. Evaluating muscle mass before surgery and implementing strategies to enhance it could lower the likelihood of urinary incontinence. This insight assists clinicians in improving risk evaluation and management when developing preoperative and rehabilitation strategies.